Integrated coastal zone management in the Venice area: A methodological framework - Frédéric Brochier; Carlo Giupponi (Fondazione Eni Enrico Mattei (FEEM), 2001)
Recent years have seen an increasing consensus on the Integrated Coastal Zone Management (ICZM) principles and structure, and the widespread recognition of its effectiveness in dealing with multiples and interconnected coastal issues. A successful ICZM programme adjusted to a specific context will incorporate systems of governance, culture and tradition, needs and expectations and will be built as much as possible on existing organisation and arrangements. This paper aims at defining the methodological basis for an ICZM framework suitable for an operational application in the socio-economic and environmental context of the Venetian area. The first section of the paper defines the basic concepts involved in coastal planning. The second section reviews methodological requirements and constraints. In the third section the paper analyses the procedure, the stages and steps within those stages that are generally necessary to implement ICZM programmes. Finally, the conclusive remarks identify further research requirements that will contribute to a concrete proposal for the Venice Lagoon System.
Keywords: O20; Q01; Q20; 330; Coastal planning; sustainable development; policy; integrated management; methodology; Venedig; Küstenschutz